2008
DOI: 10.1111/j.1365-2826.2008.01744.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Activates Brain Dopaminergic Systems in the Eel with an Inhibitory Impact on Reproductive Function

Abstract: In the eel, a deficit in gonadotrophin-releasing hormone (GnRH) and a strong dopaminergic (DA) inhibition are responsible for the blockade of gonad development if silver eels are prevented from their reproductive migration. Environmental factors that eels encounter during their oceanic reproductive migration are thought to play an important role in the stimulation of eel pubertal development. We investigated the potential role of melatonin, a known mediator of the effects of external factors on reproductive fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 111 publications
(136 reference statements)
1
53
0
1
Order By: Relevance
“…However, fish do not possess such an anatomically distinct pars tuberalis in the pituitary gland, and the involvement of melatonin in the fish reproductive cycle 232:3 is only supported by a few studies. However, effects of melatonin have been described at the hypothalamic (Popek et al 2005, Alvarado et al 2015, pituitary (Khan & Thomas 1996, Sébert et al 2008 and gonadal (Chattoraj et al 2005) levels.…”
Section: Melatoninmentioning
confidence: 99%
“…However, fish do not possess such an anatomically distinct pars tuberalis in the pituitary gland, and the involvement of melatonin in the fish reproductive cycle 232:3 is only supported by a few studies. However, effects of melatonin have been described at the hypothalamic (Popek et al 2005, Alvarado et al 2015, pituitary (Khan & Thomas 1996, Sébert et al 2008 and gonadal (Chattoraj et al 2005) levels.…”
Section: Melatoninmentioning
confidence: 99%
“…Thus, melatonin has stimulatory effects on brain dopaminergic system in eel [8]. Moreover, in the Atlantic croaker melatonin treatment increases luteinizing hormone levels, by activating the preoptic/hypothalamic areas and the pituitary gland [9].…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin acts on the reproductive system by acting on GnRH release (7,8) and thereby on gonadotropins (9). Some authors (10,11) have shown evidence of melatonin's direct action on the ovaries.…”
mentioning
confidence: 99%